Peran Layanan Bimbingan Dan Konseling Dalam Meningkatkan Kedisiplinan Siswa Smp - Ani Susanti; Slamet Riadi; Rizali Djaelangkara; Elisabeth Josephine Topiu; Ariesta Intan Navya; Muh Rizky Assalam; Shafira Anastasya; Anjelita Putri Ayudya Pasyha; Muhammad Nashrudin; Chelsea Violin Horas; Safira Safira (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Student discipline is one of the most influential factors in the success of the educational process at school, especially at the junior high school (SMP) level, which represents an important transitional phase in students’ development. At this stage, students often experience physical, emotional, and social changes that can affect their disciplinary behavior. Therefore, Guidance and Counseling (BK) services hold a strategic position in helping students to understand, adapt, and comply with the norms and rules that apply in school. This study aims to examine in depth the role of BK services in improving student discipline in junior high schools through various programs and approaches implemented by BK teachers. The research uses a qualitative descriptive method with data collection techniques that include in-depth interviews with BK teachers, observation of student behavior, and documentation studies of disciplinary records and BK programs in schools. The results show that BK services make a significant contribution to shaping disciplined behavior through several forms of services, such as basic services (orientation, information, and content mastery), responsive services (individual and group counseling), individual planning services, as well as system support involving collaboration with homeroom teachers, subject teachers, and parents. BK teachers also play a role in providing education about the importance of discipline, helping students develop self-control, and offering problem-solving approaches that are tailored to each student’s condition. In addition, BK services have proven effective in creating a conducive school environment by preventing indiscipline such as tardiness, violations of school rules, and low academic responsibility. BK programs that are designed sustainably and adapted to students’ developmental needs can increase their motivation, awareness, and commitment to school regulations. Thus, it can be concluded that BK services have a vital and effective role in improving student discipline.